PENGGUNAAN MEDIA CANVA PADA MATERI PERUBAHAN BENTUK ENERGI UNTUK MELATIH KEAKTIFAN SISWA KELAS IV B SD SUPRIYADI 01 SEMARANG - Melinda Febri Hapsari; Qoriati Mushafanah (Jurnal Binagogik, 2024)
The activity of class IV B students at SD Supriyadi 01 Semarang before the teacher used Canva media in the learning process was relatively low. This is evidenced by students' lack of focus in listening to explanations from the teacher, less active in expressing opinions, less active in question and answer activities, less participation in group discussions, and less serious in carrying out the tasks given by the teacher. Based on this description, this research aims to to find out the effect of using Canva media on material changing forms of energy in training the activity of class IV B students at SD Supriyadi Semarang. The method used in this research is a descriptive qualitative research method. The instruments used in this research are observation and documentation. This research shows that the use of Canva media in energy change material can train the activity of class IV B students at SD Supriyadi 01 Semarang.